Cover Feature: Thermotriggered Domino‐like Single‐Crystal‐to‐Single‐Crystal Phase Transition from Face‐to‐Edge to Face‐to‐Face Packing of Anthracenes (Chem. Eur. J. 70/2021). Issue 70 (7th December 2021) - Hino, Yuto; Hayashi, Shotaro
Abstract : The thermotriggered domino‐like single‐crystal‐to‐single‐crystal phase transition from the blue‐photoluminescent face‐to‐edge packed 1, 8‐bisphenylanthracene crystal to the face‐to‐face molecular packed greenish‐blue‐photoluminescent crystal was successfully observed on a fully visible timescale. More information can be found in the Full Paper by Y. Hino and S. Hayashi (DOI: 10.1002/chem.202103165 ).